Some biological data of Fenusa ulmi Sundevall, 1847 (Hymenoptera: Tenthredinidae) in Ulyanovsk region (Russia) - E.N. Yegorenkova; N.A. Lengesova; Z.A. Yefremova (Кавказский энтомологический бюллетень, 2010)
The description of features of a mining, development of larvae and a stage of weaving of cocoon of Fenusa ulmi Sundevall, 1847 in the conditions of Ulyanovsk region.